Effectiveness of Business Education Professionalism in Improving the Quality of Education - Dorathy Ogochukwu Anike (Matondang Journal, 2023)
This article discusses effectiveness of business education professionalism in improving the quality of education. The past year has witnessed an outpouring of concern that business education may be headed in the wrong direction. However, scholars differed widely in their analysis of the problem and what should be done about it. Various authors have presented interesting and provocative views about the nature of present challenges in business education. An examination of the history of higher education suggests that the path away from professionalism has not resulted primarily from proactive strategizing on the part of management educators. The study covers how to perform work amid a discourse of professionalism, effectiveness of business education professionalism, problems affecting quality educators in business education programmes, and strategies for improving business education professionalism. Although much of the research on organizational fields has examined processes by which organizations within fields came to resemble each other over time, observers also have noted that fields are often in flux and do not necessarily stabilize. It was recommended that business educators should adequately prepare and equip her students with sound professional abilities as it concern teaching ability to enable them expertly impart sound Business Education knowledge.